2008
DOI: 10.1074/jbc.m710601200
|View full text |Cite
|
Sign up to set email alerts
|

Glucose and Endoplasmic Reticulum Calcium Channels Regulate HIF-1β via Presenilin in Pancreatic β-Cells

Abstract: Pancreatic ␤-cell death is a critical event in type 1 diabetes, type 2 diabetes, and clinical islet transplantation. We have previously shown that prolonged block of ryanodine receptor (RyR)-gated release from intracellular Ca 2؉ stores activates calpain-10-dependent apoptosis in ␤-cells. In the present study, we further characterized intracellular Ca 2؉ channel expression and function in human islets and the MIN6 ␤-cell line. All three RyR isoforms were identified in human islets and MIN6 cells, and these end… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
58
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(66 citation statements)
references
References 66 publications
8
58
0
Order By: Relevance
“…We have previously shown that longterm inhibition of RyR2 in low glucose leads to programmed ␤-cell death involving calpain-10, but not caspase-3; conversely, RyR inhibition protected islets under conditions of chronic hyperglycemia (17). We have also shown that RyR inhibition significantly reduces the ratio of ATP to ADP in MIN6 ␤-cells (23), an event that could conceivably activate ER stress (24,25). Furthermore, studies of other cells types have suggested that ER stressassociated damage can be affected by inhibitors of RyRs (26) or IP 3 Rs (27).…”
mentioning
confidence: 61%
See 1 more Smart Citation
“…We have previously shown that longterm inhibition of RyR2 in low glucose leads to programmed ␤-cell death involving calpain-10, but not caspase-3; conversely, RyR inhibition protected islets under conditions of chronic hyperglycemia (17). We have also shown that RyR inhibition significantly reduces the ratio of ATP to ADP in MIN6 ␤-cells (23), an event that could conceivably activate ER stress (24,25). Furthermore, studies of other cells types have suggested that ER stressassociated damage can be affected by inhibitors of RyRs (26) or IP 3 Rs (27).…”
mentioning
confidence: 61%
“…MIN6 cells were cultured and transfected as described previously (23). Cells were imaged 48 -72 h after transfection.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, HIF-1b expression was enhanced in perinecrotic areas of spheroids, presumably as a result of glucose deficiency, which accompanies hypoxia in spheroids and is known to induce HIF-1b expression. 18 Importantly, the knockdown of one a-subunit increased the expression of the other a-subunit. Spheroids lacking one a-subunit displayed growth and survival advantages as compared to both WT and b-knockdown spheroids.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, the presence of RyRs in insulin secreting β-cells is well-accepted at the present time, although the expression of each type of RyRs is variable, depending on the species studied. The mRNAs for the three types of RyRs have been detected in human β-cells, whereas mRNA for RyR2 but not RyR1 was detected in INS-1 cells and rat islets using RT-PCR methods [18][19][20]. Since there is still no clear consensus on the role of RyR in stimulus-secretion coupling in β-cells, we determined, using in-sulin secreting rat pancreatic β-cells (INS-1 …”
Section: Elevation Of the Intracellular Free Calcium Concentration ([Camentioning
confidence: 99%